The Relationship Between Family Support and Psychological-Well-Being on Honorary Teachers in Sidoarjo: Hubungan Antara Dukungan Keluarga dengan Psychological-Well-Being pada Guru Honorer di Sidoarjo - Santika, Firda Nara; Mariyati, Lely Ika (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to determine the relationship between family support and psychological well-being for honorary teachers in Taman District, which means that there are two variables in this study, namely: family support as variable X and psychological well-being as variable Y. This study includes research correlational quantitative. The sample in this study was 100 honorary teachers from 125 honorary teachers as a population in 4 high school and equivalent in Taman sub-district. The sampling technique used in this study was purposive sampling. The data collection technique in this study used 2 scales, namely the family support scale consisting of 34 items with 0.953 reliability and the psychological well-being scale consisting of 33 items with 0.936 reliability. The hypothesis in this study is that there is a positive relationship between family support and the psychological well-being scale for honorary teachers in Taman District. The results of this study indicate that the correlation coefficient is 0.852 with a significance value of 0.000 <0.05. These results indicate that the hypothesis proposed in this study is accepted. While the results of the coefficient of determination test are 0.722 (Adjusted R Square) which shows that the family support variable contributes 72.2% to the psychological well-being variable.